2014
DOI: 10.1186/1479-5876-12-36
|View full text |Cite
|
Sign up to set email alerts
|

Combined PD-1 blockade and GITR triggering induce a potent antitumor immunity in murine cancer models and synergizes with chemotherapeutic drugs

Abstract: BackgroundThe coinhibitory receptor Programmed Death-1 (PD-1) inhibits effector functions of activated T cells and prevents autoimmunity, however, cancer hijack this pathway to escape from immune attack. The costimulatory receptor glucocorticoid-induced TNFR related protein (GITR) is up-regulated on activated T cells and increases their proliferation, activation and cytokine production. We hypothesize that concomitant PD-1 blockade and GITR triggering would synergistically improve the effector functions of tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
125
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(133 citation statements)
references
References 40 publications
6
125
0
1
Order By: Relevance
“…This is a key consideration in light of the impressive efficacy of combined checkpoint blockade with nivolumab (anti-PD-1) and ipilimumab (anti-CTLA4) in melanoma patients (24) as well as numerous preclinical studies that have demonstrated synergy between antibodies targeting PD-1:PD-L1 and additional immunomodulatory pathways, such as TIM-3 (25), LAG-3 (26), GITR (27), OX-40 (28), and 4-1BB (29). In the case of HAC-PD-1, multispecific agents targeting synergistic immunomodulatory pathways can readily be elaborated by simply fusing multiple small protein modules, including other engineered receptor decoys or single-domain antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…This is a key consideration in light of the impressive efficacy of combined checkpoint blockade with nivolumab (anti-PD-1) and ipilimumab (anti-CTLA4) in melanoma patients (24) as well as numerous preclinical studies that have demonstrated synergy between antibodies targeting PD-1:PD-L1 and additional immunomodulatory pathways, such as TIM-3 (25), LAG-3 (26), GITR (27), OX-40 (28), and 4-1BB (29). In the case of HAC-PD-1, multispecific agents targeting synergistic immunomodulatory pathways can readily be elaborated by simply fusing multiple small protein modules, including other engineered receptor decoys or single-domain antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…For years cytostatic drugs were considered to be detrimental for immunity, as toxic effects on lymphocytes are a commonly observed side-effect. Still, studies point towards the synergy between TIL reactivation by blocking PD-1 (which suppresses CTL activation) and glucocorticoid-induced TNFR related protein (GITR) (which additionally stimulates T cells) and chemotherapeutics (paclitaxel or cisplatin) [139][140][141]. These and other stories of enemies becoming allies were recently picked up by material scientists, who packaged these synergistic components into single NPs.…”
Section: Immunogenic Cell Deathmentioning
confidence: 99%
“…Combined anti-PD-1 blockage and GITR costimulation has potent antitumor activity in murine ID8 ovarian cancer model and is synergistic with chemotherapeutic agents. This combination promotes accumulation of CD4, CD8 T cells with decreased Treg and myeloid derived suppressive cells [111]. TRX518, an anti-GITR mAb, is being studied in a Phase I study in patients with stage III or stage IV melanoma or other solid tumor malignancies (NCT01239134 [86]).…”
Section: Gitrmentioning
confidence: 99%